(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2023)
For many students, COVID-19 has created new barriers to obtaining a degree while also making existing restrictions more difficult to overcome. COVID-19 has had a financial, academic, and emotional toll on individuals who are already seeking a degree. However, preliminary research suggests that these effects differ for students who had the greatest barriers to joining and remaining in institutions prior to the pandemic, particularly those from historically impoverished and marginalised populations. This study investigates the financial management practices among technical students in Malaysia’s Higher Institution of during COVID-19 pandemic. 610 students were given a survey questionnaire by way of basic random sample techniques covering TVET public university, polytechnics, and community college. The tools encompass the knowledge, literacy, and attitude components of the financial management construct. The results demonstrate that technical students average highly in financial understanding. The two concepts of planning and financial management are closely related. Students should manage their funds effectively and learn how to spend money sensibly if they want to succeed in the hard world that lies ahead. Bagi kebanyakan pelajar, COVID-19 telah mencipta halangan baru untuk memperoleh ijazah dan juga menjadikan sekatan yang ada lebih sukar untuk diatasi. COVID-19 telah memberi kesan kewangan, akademik, dan emosi kepada individu yang sudah memiliki ijazah. Walau bagaimanapun, penyelidikan awal menunjukkan bahawa kesan ini berbeza bagi pelajar yang mempunyai halangan terbesar untuk menetap di institusi sebelum wabak, terutama dari populasi yang miskin dan terpinggir. Kajian ini menyiasat amalan pengurusan kewangan dalam kalangan pelajar teknikal di Institusi Tinggi Malaysia semasa pandemi COVID-19. Seramai 610 pelajar diberi soal selidik melalui teknik sampel rawak mudah yang merangkumi universiti awam (Technical and Vocational Education) TVET, politeknik, dan kolej komuniti. Soal selidik ini merangkumi pengetahuan, literasi, dan komponen sikap dalam pengurusan kewangan. Hasilnya menunjukkan bahawa pelajar teknikal rata-rata sangat memahami kewangan. Kedua-dua konsep perancangan dan pengurusan kewangan berkait rapat antara satu sama lain. Kajian ini diharapkan agar pelajar harus menguruskan dana mereka dengan berkesan dan belajar bagaimana membelanjakan wang dengan bijak sekiranya mereka ingin berjaya dalam dunia yang semakin sukar pada masa akan datang.